2016
DOI: 10.1126/sciadv.1601414
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of a divalent/tetravalent metal-storing atom-mimicking dendrimer

Abstract: The phenylazomethine dendrimer exhibits “atom mimicry,” and its polymerization (and Lewis acid accumulation) is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In comparison to traditional linkers, dendrimers represent a class of macromolecules with well‐defined 3D branched structure exhibiting a high degree of functionality and versatility. Dendrimers featuring multiple “wedges” and dendrons featuring single “wedge” are not only well defined as structural building blocks, but also have controllable sizes ranging from 1 to 30 nm depending on their generation . In particular, dendrimer–nanoparticle conjugates have been attracting considerable interest in medicine, drug delivery, vapor sorption, diagnostics, and electrochemical biosensors for enzyme immobilization .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to traditional linkers, dendrimers represent a class of macromolecules with well‐defined 3D branched structure exhibiting a high degree of functionality and versatility. Dendrimers featuring multiple “wedges” and dendrons featuring single “wedge” are not only well defined as structural building blocks, but also have controllable sizes ranging from 1 to 30 nm depending on their generation . In particular, dendrimer–nanoparticle conjugates have been attracting considerable interest in medicine, drug delivery, vapor sorption, diagnostics, and electrochemical biosensors for enzyme immobilization .…”
Section: Introductionmentioning
confidence: 99%
“…For G2, two sets of signals are observed that are ascribed to different phosphorus atoms of the inner and outer triethylphosphine ligands. 31 P NMR spectrum of G3 also displays two signals because the signals of two outer triethylphosphine ligands could not be well distinguished. Notably, the sharp NMR signals along with the solubility of these species have ruled out the formation of organometallic polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the precursor 1 is very stable and soluble in common solvents, which could simplify the subsequent reaction and puri cation processed during the dendrimer growth 31 . The Cu(I)-catalyzed coupling reaction of 1 with 1,3,5-triethynylbenzene produced the rst-generation DTE dendrimer G1 at yield of 73% (Scheme S3, Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this dendrimer has a capability for the precise accumulation for various metal ions [ 12 ] and organic molecules [ 13 , 14 ] in the interior. Therefore, it is a suitable molecule with many potential post-functionalization such as templated cluster synthesis [ 15 , 16 , 17 , 18 , 19 ], molecular shape recognition [ 11 ], anisotropic charge transfer [ 10 , 20 , 21 , 22 ], and further extension of the structural dimensions [ 23 , 24 ]. The dendrimer 1 ( Figure 1 ) was synthesized according to a literature method [ 9 ] and deposited on the atomically flat surfaces of substrates including mica, HOPG (highly ordered pyrolytic graphite), and Au(111).…”
Section: Resultsmentioning
confidence: 99%